A review of capital budgeting practices developed and developing country context - Pratheepkanth, P. (University of Jaffna, 2018)
The main purpose of this paper is to analyse existing literature the use of capital budgeting practices by firms in a comparative perspective to see whether any differences between developed and developing countries context. Trends towards sophisticated techniques have continued in developed and developing countries; though, developed countries, most of the firms are using sophisticated capital budgeting techniques however, that even though over time the use of the simple techniques method has declined as a primary tool for investmentevaluation. In context of developing countries most frequently employ with non‐discountedcash flow techniques and discounted cash flow techniques. The study notes there still remains a difference between developed and developing countries and theory‐practice gap in the sophisticated capital budgeting techniques, and simple capital budgeting techniques. What this study suggestions is that the difference between developed and developing countries firms is smaller than might have been expected based upon the differences in the level of economic height, at least with respect to the use of sophisticated techniques as investment appraisal tool.
Keywords: Capital budgeting practices; Developed countries; Developing countries